Factors Affecting Consumer Behavior of Fast Food in Pathum Thani - Khaipetch, Janati (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2017)
The purpose of this research was to study factors affecting consumer behavior of fast food. There were 200 samples chosen from people who lived in Pathum Thani by convenient sampling method. The data were statistically analyzed by using descriptive statistics comprising frequency, percentage, mean, and standard deviation and inferential statistics including Independent Samples t-test, One-Way ANOVA, Chi-square, and Correlation. The results revealed that the majority of respondents were female, had age range more than 35 years old, and earned a bachelor’s degree. The most popular fast food brand of respondents was KFC. In addition, most of respondents normally bought in store, and the reason to buy was convenience. The results of hypothesis testing between demographics and consumer behavior revealed that gender, age, education, occupation, and income were associated with reason to buy fast food. Occupation and income were associated with brand preference while education and occupation were associated with channel to order fast food. Besides, age and occupation caused differences in frequency per month and budget per time. The results of hypothesis testing between the marketing mix and consumer behavior showed that product and place affected reason to buy while place and promotion affected brand preference at a significance level of 0.05.